(untitled) (San Francisco, CA, 2007)
Contains sermons for the entire year and lectionary messages and worship aids to expand Sunday services. This manual features: articles that speak to the hearts and minds of ministers; a treasury of practical, contemporary and relevant sermon illustrations; and lectionary based children's sermons for engaging young minds.
Keywords: Pastoral theology,Thần học mục vụ; Handbooks, manuals, etc.,Sổ tay, sách hướng dẫn, vv